2002
DOI: 10.2337/diabetes.51.8.2530
|View full text |Cite
|
Sign up to set email alerts
|

Islet Hyperperfusion During Prediabetic Phase in OLETF Rats, a Model of Type 2 Diabetes

Abstract: Although it has been hypothesized that initial hyperperfusion followed by late hypoperfusion in islet circulation occurs in rodent models of type 2 diabetes, islet blood flow has not been measured during prediabetic phase. We studied islet blood flow in Otsuka Long-Evans Tokushima Fatty (OLETF) rats, a model of slowly progressive obese type 2 diabetes. Islet blood flow was measured by the two-color microsphere method under anesthesia at different ages. Islet blood flow was significantly higher in young OLETF r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…The reasons for the discrepancy between these studies are not known. Compared to most studies on islet blood flow in adult rats [1,10,12,31,32] one group [14] obtained a considerably lower value (~2% vs 7-20%) for the control rats. Such low islet blood flow values have previously only been recorded in very young animals [16,33,34].…”
Section: Discussionmentioning
confidence: 72%
“…The reasons for the discrepancy between these studies are not known. Compared to most studies on islet blood flow in adult rats [1,10,12,31,32] one group [14] obtained a considerably lower value (~2% vs 7-20%) for the control rats. Such low islet blood flow values have previously only been recorded in very young animals [16,33,34].…”
Section: Discussionmentioning
confidence: 72%
“…A study on hyperglycemic Goto-Kakizaki (GK) rats showed that following a 60% pancreatectomy, GK rats are unable to compensate for decreased beta-cell mass by increasing islet blood flow in contrast to normal animals [15] . And islet hyperperfusion during the pre-obese and pre-diabetic state was found in a rat model of obesity and type 2 diabetes [16] . Islet hypoperfusion was noted in long-term hyperglycemia [17] .…”
Section: Discussionmentioning
confidence: 99%
“…5). Whether the glucose-induced increase in islet blood flow may be detrimental under pathological states like chronic hyperglycemia is not known (11). Likewise, the reduced islet blood flow during hypoglycemia suggests that a glucose level below the physiological range slows insulin delivery into the systemic circulation, as would be desired during hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%